2020
DOI: 10.15547/ast.2020.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Fall Armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae): A recent threat and future management strategy in Nepal

Abstract: Abstract. Fall Armyworm (FAW), Spodoptera frugiperda, is an invasive pest of maize including other cultivated crops such as rice, wheat, and many other vegetables. This invasive species was initially noticed in North-America and later reported in many countries of Africa in early 2016. In South Asia, this has been reported for the first time in India followed by Srilanka in 2018 and Bangladesh, China, Taiwan and Nepal in 2019. It is polyphagous in nature and damage has been reported in more than 80 plant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…Several previous studies have explained about the invasion, distribution, life cycle and management of the pest (Bhusal & Bhattarai, 2019;Bhusal & Chapagain, 2020;Gahatraj et al, 2020;Gc et al, 2019). However, there are scanty literatures that explains about the efficacy of various management strategies that could been practiced for experimental research in Nepal (Bhusal & Bhattarai, 2019;Gahatraj et al, 2020). Findings from this review will be useful for the academicians, extension workers and plant protectionist to design a sustainable FAW management protocol.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several previous studies have explained about the invasion, distribution, life cycle and management of the pest (Bhusal & Bhattarai, 2019;Bhusal & Chapagain, 2020;Gahatraj et al, 2020;Gc et al, 2019). However, there are scanty literatures that explains about the efficacy of various management strategies that could been practiced for experimental research in Nepal (Bhusal & Bhattarai, 2019;Gahatraj et al, 2020). Findings from this review will be useful for the academicians, extension workers and plant protectionist to design a sustainable FAW management protocol.…”
Section: Introductionmentioning
confidence: 92%
“…FAO (2019) warned the threat and risk of invasion of FAW in Nepal since its invasion in India and believed the loss could reach 100% in maize crop. It has also been reported that there will be a greater risk of FAW if no management tactics are applied in Nepal (Bajrachharya et al, 2019;Gahatraj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La infestacio n de larvas de Spodoptera frugiperda causa dan o foliar, llegando a ocasionar pe rdidas significativas en la produccio n del grano de maí z (Toma et al, 2017;Ramirez et al, 2018). Teniendo en cuenta solo el maí z, arroz, trigo (Gahatraj et al, 2020), sorgo, can a de azu car, se ha calculado que, el gusano cogollero del maí z, podrí a causar hasta 13 000 millones de do lares al an o en pe rdidas de cultivos en el Á frica subsahariana (SSÁ) (Ábrahams et al, 2017). En el a rea de distribucio n invadida por el gusano cogollero la amenaza sera duradera por la presencia de plantas hospederas y por las condiciones clima ticas favorables para la reproduccio n (Midega et al, 2018); Montezano et al, 2018).…”
Section: Introductionunclassified
“…Scouting a maize field for assessing the FAW infestation level is key to the decision of deploying curative control methods. This enables early alerts and promotes effective use of insecticides by indicating to farmers when and most importantly when not to apply insecticides based on calculations of intervention thresholds, which to the best of our knowledge are only based on expert opinion for FAW in countries of recent invasion [3][4][5] in African, Asian and Australian continents.…”
Section: Introductionmentioning
confidence: 99%